Sustainable dehydration of onion slices through novel microwave hydro-diffusion gravity technique. (February 2016) - Khan, Muhammad Kashif Iqbal; Ansar, Muhammad; Nazir, Akmal; Maan, Abid Aslam
Abstract: Onion is a semi-perishable commodity having prominent nutritional value. The deterioration of onion during storage can lead to huge amount of post-harvest losses. Shelf life can be increased through drying, which also facilitates transportation, storage, and packaging due to reduced weight and volume. In the present study, a novel microwave-assisted drying technique called microwave hydro-diffusion gravity was investigated for process optimization and compared with conventional drying techniques. Results indicated that 400 W and 14 min of process were the best combination for drying that removed 80% moisture present in slices. The overall drying time of onion slices was significantly reduced (about six times) compared to hot air oven and freeze-drying methods. MHG dehydration prevented the burning of onions and maintained their sensorial attributes especially color and texture. Similarly, MHG in combination with hot air oven consumed only 0.5 MJ energy as compared to 3.24 and 3 MJ energy used by hot air oven and freeze drying, respectively. In short, results proved that MHG technique is much better than conventional techniques in terms of end product quality and process efficiency. Industrial relevance: Microwave hydro-diffusion technology is optimized for onion drying. This technology will help in reducing the use of energy and will avoid the loss of water soluble components. These bioactive components have great importance in the field of pharmaceutical. Thus, this technology simultaneously dries the product and extracts the valuable components. It will increase the process efficiency and reduce the processing cost. Highlights: Microwave hydro-diffusion gravity reduces the loss of water soluble component during dehydration. MHG reduced the drying time and energy consumption. MHG has non-significant influence on sensorial attributes of dried onion slices.